Robust Estimation of Neural Signals in Calcium Imaging - Inan, Hakan; Erdogdu, Murat; Schnitzer, Mark (31st Conference on Neural Information Processing Systems (NIPS 2017), 2017)
Calcium imaging is a prominent technology in neuroscience research which allows for simultaneous recording of large numbers of neurons in awake animals. Automated extraction of neurons and their temporal activity in imaging datasets is an important step in the path to producing neuroscience results. However, nearly all imaging datasets typically contain gross contaminating sources which could be contributed by the technology used, or the underlying biological tissue. Although attempts were made to better extract neural signals in limited gross contamination scenarios, there has been no effort to address contamination in full generality through statistical estimation. In this work, we proceed in a new direction and propose to extract cells and their activity using robust estimation. We derive an optimal robust loss based on a simple abstraction of calcium imaging data, and also find a simple and practical optimization routine for this loss with provably fast convergence. We use our proposed robust loss in a matrix factorization framework to extract the neurons and their temporal activity in calcium imaging datasets. We demonstrate the superiority of our robust estimation approach over existing methods on both simulated and real datasets.